The Future of Fun : Integrating Facilities and Services Quality to Enhance The Sustainability of Visitor Satisfaction in Amusement Park Industry: Masa Depan Hiburan: Integrasi Kualitas Fasilitas dan Layanan untuk Meningkatkan Keberlanjutan Kepuasan Pengunjung dalam Industri Taman Hiburan. - Liandro Lie; Sri Rezeki (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
The amusement park industry is experiencing rapid growth, driven by rising consumer expectations and an increasing emphasis on sustainability. This study explores the integration of facility quality and service quality as a strategic approach to enhancing long-term visitor satisfaction within the amusement park sector. Grounded in the SERVQUAL model and the principles of sustainable service design, the research investigates how the synergy between physical infrastructure and human-centered service delivery influences visitor satisfaction and loyalty. A mixed-methods approach was employed, combining quantitative survey data from amusement park visitors with qualitative insights derived from management interviews. The findings reveal that both facility quality and service quality significantly impact visitor satisfaction, with service quality exerting a more direct effect. Furthermore, sustainability practices embedded within these elements function as mediators that strengthen visitors’ trust and their intention to revisit. This study underscores the importance of holistic and integrated strategies for amusement parks aiming to sustain competitive advantage and foster long-term relationships with visitors in an increasingly experience-driven economy.